2016
DOI: 10.1259/bjr.20150810
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of standard axial 64-slice chest CT compared to cardiac MRI for the detection of cardiomyopathies

Abstract: Objective: To assess the diagnostic accuracy of standard axial chest CT compared with cardiac MRI for cardiomyopathies. Methods: The standard axial 64-slice chest CTs of 49 patients with cardiomyopathies and 27 controls were blindly assessed for the presence of a cardiomyopathy by two independent readers. Qualitative and quantitative analysis included assessment of: (i) interatrial septal thickness, (ii) left atrial diameter, (iii) myocardial hypertrophy, thinning or fat, (iv) myocardial and papillary muscle c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…LV transverse diameter has been previously investigated for the identification of LVE [4][5][6]. In two previous studies in which echo-cardiography was used as the reference standard [4,5], the investigators recommended LV transverse diameter thresholds of 55-56 mm for detection of LVE, which are similar to the threshold values identified in our study.…”
Section: Eifer Et Alsupporting
confidence: 79%
See 3 more Smart Citations
“…LV transverse diameter has been previously investigated for the identification of LVE [4][5][6]. In two previous studies in which echo-cardiography was used as the reference standard [4,5], the investigators recommended LV transverse diameter thresholds of 55-56 mm for detection of LVE, which are similar to the threshold values identified in our study.…”
Section: Eifer Et Alsupporting
confidence: 79%
“…In two previous studies in which echo-cardiography was used as the reference standard [4,5], the investigators recommended LV transverse diameter thresholds of 55-56 mm for detection of LVE, which are similar to the threshold values identified in our study. A smaller study of LV transverse diameter on CT in a population of patients with cardiomyopathy and MRI as the reference standard [6] showed that an LV transverse diameter threshold of 47 mm had specificity of 100% and sensitivity of 47% for the diagnosis of dilated cardiomyopathy. In contrast to these studies in which LV transverse diameter was measured at the midventricular level, in our study the largest transverse diameter was measured at any level to maximize sensitivity.…”
Section: Eifer Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…As a result of our study, it was shown that the measurements of cardiac chambers in coronary CTA and non-ECG-gated, unreformed contrast-enhanced thoracic CT are perfectly compatible with each other. In the literature, there are several studies evaluating the dimensions of the heart chambers with coronary CTA (18)(19) or with non-ECG-gated thoracic CT (20) . However, in the English literature review, there was no study which was measured the diameter and area of the cardiac chambers in thoracic CT and coronary CTA and comparing them with each other.…”
Section: Discussionmentioning
confidence: 99%